Kompetensi Profesional Guru Pendidikan Agama Islam Dalam Meningkatkan Hasil Belajar Siswa - Julhadi, Julhadi; Rahmi, Fitri; Ritonga, Mahyudin (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research the challenge faced by Islamic Religious Education as a subject is how to implement it, not only teaching knowledge about religion, but how to direct students to have the qualities of faith, piety and noble morals. This research aims to evaluate the professional competence of teachers of Islamic Religious Education (PAI) in MAN 1 Solok Plus Skills in mastering teaching materials, use of learning media, and implementation of learning evaluation. The school has a good reputation for achieving achievements in the district of Solok, being a reference in some ways. Researchers want to explore how well the professional competence of teachers of Information Education is obtained from various sources, such as the head of the madrasah, teachers, and students of the 12th grade of religious major. Data collection methods include observations, interviews, and documentation. The data was then analyzed with data reduction techniques, data display, and Islamic Religion (PAI) data verification at this school. This research will use descriptive qualitative methods. The study showed that the teachers of Islamic Religious Education at MAN 1 Solok have solid skills in mastering the learning material, the use of relevant media, as well as the evaluation of learning to improve student achievement. Hopefully, this research could encourage other researchers to investigate similar topics in different contexts or fields of study.